Visual and Linguistic Stimuli in the Remote Associates Test: A Cross-Cultural Investigation - Toivainen, Teemu; Olteteanu, Ana-Maria; Repeykova, Vlada; Likhanov, Maxim; Kovas, Yulia (Frontiers in Psychology, 2019)
The Remote Associates Test (RAT) is a measure of associative ability, which is often regarded as essential for creative thinking. The most commonly used version of the test is the compound RAT. However, many RAT items do not translate directly in different languages. Additionally, a linguistic measure cannot be used to measure visual associative ability. A visual measure for associative ability that is similar to the RAT would be a useful tool for cross-cultural investigations of creativity. The present study investigated the relationship between the linguistic and a newly developed visual version of RAT in Russian and Finnish native speakers (for both samples n = 67). Both linguistic and visual measures showed good internal reliabilities in both samples (Cronbach’s α = 0.73–0.84). The mean score in the visual task was slightly higher for the Finnish sample. The correlation between the two measures was stronger in the Russian sample (r = 0.56) compared to the Finnish sample (r = 0.28). These results are discussed in relation to linguistic and cultural differences between the samples.